Analisa Pengaruh Marketing Mix Terhadap Minat Beli Konsumen akan Produk Mie Lopo Timor Melalui Motivasi Sebagai Variable Intervening - wandy, jonathan (Jurnal Strategi Pemasaran, 2014)
Abstract â The growth of business enganged in the industry are now develop well. As the only one industry of noodle has begun in Kupang, NTT, CV. Usaha Timor Makmur have competence with many product fromÂ  another islands, like java and Sulawesi. The good marketing mix strategy canÂ  make good motivationÂ  thenÂ  make purchase intention the consumen. This research are create for analyze marketing mix influence to purchase intention through motivation as variable intervening with spread 100 questionnaire to responden who buy and consume Mie Lopo Timor product. This research using quantitative mothod. Using structural equationÂ  method model â partial least square SEM â PLS. Research show that marketing mix influences motivation and motivation influences purchase intention of customer.